Техніка юридичного письма в нормативно-правових актах - Онищук, Ігор Ігорович (Національний університет "Львівська політехніка", 2012)
Роботу присвячено комплексному загальнотеоретичному дослідженню юридичного письма та розробці концепції техніки юридичного письма в нормативно-правових актах як сегмента юридичної техніки та складової юридичних технологій. У межах дослідження доктринальних основ техніки юридичного письма розглянуто стан наукового вивчення проблеми, понятійно-категоріальний апарат і нормативно-правове регулювання вимог до юридичної техніки в Україні. Здійснено загальнотеоретичну характеристику техніки юридичного письма. Розглянуто види юридичного письма, його стиль і тональність. Обґрунтовано техніку та логіку письмового викладу. Розкрито поняття, зміст і внутрішню будову техніки юридичного письма на єдиних методологічних засадах. Встановлено критерії якості та основні правила техніки юридичного письма. Зображено модель юридичного письма. Внесено пропозиції та рекомендації щодо вдосконалення техніки юридичного письма під час розробки нормативно-правових актів. У рамках дослідження документального вираження змісту нормативно-правового акта висвітлено особливості мови та системи лінгвістичних засобів, юридичних конструкцій та конструювання, термінології та законодавчих дефініцій. З’ясовано причини юридичних помилок та запропоновано способи їх розпізнавання. Работа посвящена комплексному общетеоретическому исследованию юридического письма и разработке концепции техники юридического письма в нормативно-правовых актах как сегмента юридической техники и составляющей юридических технологий. В рамках исследования доктринальных основ техники юридического письма рассмотрено состояние научного изучения проблемы, понятийно-категориальный аппарат и нормативно-правовое регулирование требований к юридической техники в Украине. Проведено общетеоретическую характеристику техники юридического письма. Рассмотрены виды юридического письма, его стиль и тональность. Обосновано технику и логику письменного изложения. Раскрыто понятие, содержание и внутреннее строение техники юридического письма на единых методологических принципах. Установлены критерии качества и основные правила техники юридического письма. Изображена модель юридического письма. Внесены предложения и рекомендации по совершенствованию техники юридического письма при разработке нормативно-правовых актов. В рамках исследования документального выражения содержания нормативно-правового акта освещены особенности языка и системы лингвистических средств, юридических конструкций и конструирования, терминологии и законодательных дефиниций. Выяснены причины юридических ошибок и предложены способы их распознавания. The work is devoted to general theoretical investigation of complex legal writing and developing the concept of technology in legal writing regulations as the segment of legal technique and legal component technologies. Within the study doctrinal foundations engineering legal writing the state of the scientific study of the problems of concepts and categories of normative and legal regulation of the legal technique in Ukraine. Done general theoretical characterization of legal writing technique. Considered the types of legal writing, his style and tone. Grounded the technique and logic of written statement, the quality criteria and the basic rules of legal writing technique. Depicted model of legal writing. Submitted the suggestions and recommendations for improving of legal writing technique. Revealed the features of the language and system of linguistic means, legal constructions and designing, legal terminology and definitions. The reasons for legal errors and the ways of their recognition were found. The scientific novelty of the research lies in the fact that the nation's first comprehensive theory of law carried out monographic study of the legal writing technique, it formed an integral detailed concept. Formulated the author's definition of legal writing as an art form of writing, which is used by lawyers, judges, notaries, parliamentarians, officials, managers, civil society, for the content of the written expression of legal acts, processing of legal documents, legal analysis of the expression of legal rights and responsibilities. Justified by the notion of technology as part of the legal technology, legal form of thinking and professional system of legal rules, tools, techniques and methods that are used to provide a written construction, constructive and perfect laws and regulations. The necessity of a systematic and clear legal and regulatory requirements for legal technology and the legal acts to provide by law. Developed recommendations for the correct use of terms in the legal acts, which are based on the following requirements, as linguistic correctness, consistency, accuracy, concise, definitive, terminological unity, emotional and expressive neutrality. Courtesy of the author’s vision of the legal writing technique improving to the legal acts, which is based on compliance with the requirements of the legislative style, the professional development of participants in the lawmaking process of the legal tools technique and technologies, including in contemporary legal education of a special course of legal writing techniques to develop writing skills a lawyer. The scientific value of the thesis is to develop an integrated concept of legal writing technique. This implementation is a significant contribution to the theory of legal technique as an independent scientific discipline in the system of jurisprudence. The practical value of research is the ability to use the provisions made – to protect and theoretical conclusions of the thesis to improve the quality of the Ukraine regulations in research activities, the analysis of current state and prospects of the most important principles of legal technique in terms of language and style regulatory acts, in the process of teaching the theory of law and more.
Техника юридического письма в нормативно-правовых актах
Legal writing technique in legal acts
Keywords: юридична техніка; юридичні технології; юридичне письмо; техніка юридичного письма; нормативно-правовий акт; юридична конструкція; юридичне конструювання; мова права; юридическая техника; юридическая технология; юридическое письмо; техника юридического письма; нормативно-правовой акт; юридическая конструкция; юридическое конструирование; язык права; legal technique; legal technology; legal writing; legal writing technique; legal act; legal structure; legal construction; the language of law